ANALISIS KEMAMPUAN PESERTA DIDIK DALAM MENYELESAIKAN SOAL HOTS KELAS XI SMAN 2 SUNGAI RAYA - Kusdianti, Indri; Sitompul, Stepanus Sahala; Mahmuda, Diah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the average level of ability of students in solving High Order Thinking Skills (HOTS) according to Bloom's Taxonomy the results of the revision, namely C4, C5 and C6 and know the mistakes made in resolving the matter of HOTS by using the troubleshooting steps Heller. This research is a descriptive qualitative research with the use of test and interview as data collection method. The subject in this research amounted to 97 students that is all students of class XI MIA SMA Negeri 2 Sungai Raya. The results obtained by stating that the average ability of learners to solve the problems HOTS by 14 %. With the average level at each level of cognitive at the level of kogniti C4 by 10%, C5 by 19% and C6 by 12%, all of which are included in the category of very low. Interviews conducted to know about the HOTS difficulties in completing the matter of HOTS based on the troubleshooting steps Heller stated the average learners are able to in the activities understand the problem, but are less able in the activity make a plan or design of a problem-solving strategy, carry out the calculation, and re-examine the correctness of the results or solutions. Thus, this research is expected of students trained in resolving a matter with a higher level in accordance with the demands of the 2013 curriculum.Â Keywords: Harmonious Vibration, Heller Problem Solving, High Order Thinking Skill.